Towards an Abyssal Praxis in 5 Moves. Issue 4 (December 2021) - Spinelli, Miro
Abstract : The equivalency "land is to soil as body is to flesh" is a guide to reflect on the techniques of coloniality in the extraction and violation of matter. From the perception that body and land are invented even as they are stolen, we endeavor to stay on the edge of that paradoxical abyss long enough to foresee modes of radical imagination.